Concrete with adjustable air permeability and preparation method thereof

By adding specific components to the concrete, an adjustable carbon nanotube fiber thin layer and pore regulator structure is formed, the problem of insufficient breathability of existing concrete materials is solved, and the effect of automatically adjusting breathability according to environmental conditions is achieved, which improves the comfort of the indoor environment and the service life of the building.

CN119661135AActive Publication Date: 2025-03-21SUINING TAINING BUILDING MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411892008.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing concrete materials lack good breathability, which makes it difficult to discharge moisture, causing problems such as indoor humidity and mold growth, and cannot automatically adjust the breathability according to changes in environmental conditions.

Method used

By adding inorganic adhesives, mineral particles, pore regulators, carbon nanotubes and synthetic fibers to the concrete, the internal pore structure of the carbon nanotube fiber thin layer and pore regulators is formed, and the breathability is automatically adjusted according to changes in ambient humidity and temperature.

Benefits of technology

It realizes automatic air permeability adjustment of concrete, effectively deals with moisture problems, improves indoor environment comfort, and increases the service life of the building while ensuring structural strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200872250000051
    Figure BDA0005200872250000051
  • Figure BDA0005200872250000052
    Figure BDA0005200872250000052
  • Figure BDA0005200872250000061
    Figure BDA0005200872250000061
Patent Text Reader

Abstract

The invention relates to the field of novel building materials, in particular to air permeability adjustable concrete and a preparation method thereof. The invention provides a concrete raw material with adjustable air permeability. The concrete raw material comprises concrete; an inorganic adhesive; mineral particles; a pore regulator; carbon nanotubes and synthetic fibers. Wherein the concrete, the inorganic adhesive and the mineral particles are used as base materials, and then the air hole regulator, the carbon nanotubes and the synthetic fibers are added at a certain temperature, so that the concrete with adjustable air permeability is prepared. The invention further provides a preparation method of the concrete with the adjustable air permeability. The preparation method comprises the two steps of S1, base material mixing and S2, preparation of the concrete with the adjustable air permeability. The pore regulator is uniformly distributed in the concrete produced by the preparation method, a carbon nanotube fiber thin layer is generated on the surface, and the air permeability can be regulated by combining the pore regulator and the carbon nanotube fiber thin layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of novel building materials, and in particular to concrete with adjustable air permeability and a preparation method thereof. Background Art

[0002] With the rapid development of building technology, modern buildings have raised their pursuit of indoor environmental comfort to an unprecedented level. Most existing concrete materials on the market, although excellent in structural strength, have obvious shortcomings in terms of air permeability, especially in environments with heavy humidity. As these materials lack good air permeability, moisture is difficult to be effectively discharged, which in turn causes a series of problems such as indoor humidity and mold growth, which not only threatens the structural safety of the building, but also greatly shortens the service life of the building, seriously affecting the overall comfort of the indoor environment.

[0003] In response to this problem, the industry has begun to develop building materials with better air permeability in order to improve the indoor environment. However, existing breathable building materials generally have the problem of fixed air permeability and cannot automatically adjust their air permeability according to changes in environmental conditions, making it difficult to meet the diverse needs for air permeability in different seasons and climate conditions. This limitation undoubtedly limits the flexibility and adaptability of building materials in practical applications.

[0004] Therefore, it is necessary to develop a concrete material that can automatically adjust its air permeability according to changes in ambient humidity. This new type of concrete can not only effectively deal with moisture problems and improve the comfort of the indoor environment, but also give building materials higher intelligence and adaptability while ensuring structural strength, bringing revolutionary breakthroughs to the field of modern construction. Summary of the invention

[0005] In view of the above-mentioned existing technical problems, the present invention provides a concrete with adjustable air permeability and a preparation method thereof. The concrete with adjustable air permeability prepared by this method can not only ensure the structural strength, but also automatically adjust the air permeability according to the change of environmental humidity, thereby increasing the service life of the building.

[0006] The present invention discloses a concrete with adjustable air permeability, comprising the following components in parts by weight:

[0007] 35-50 parts of concrete; 5-7 parts of inorganic adhesive; 5-6 parts of mineral particles; 3-5 parts of pore regulator; 8-11 parts of carbon nanotubes; and 5-8 parts of synthetic fibers.

[0008] Preferably, the inorganic binder is a silicate.

[0009] Preferably, the mineral particles are mineral materials with high porosity, and quartz, bentonite, and calcareous minerals are further selected.

[0010] Preferably, the pore regulator is expanded microspheres, ultrafine silica fume or a combination thereof.

[0011] Preferably, the carbon nanotubes have a diameter of 10 to 50 nm and a length of 20 to 100 μm.

[0012] The present invention also discloses a method for preparing concrete with adjustable air permeability, comprising the following steps:

[0013] S1 base material mixing: concrete, inorganic adhesive and mineral particles are added to a mixer in sequence and stirred, and a base material mixture is obtained after stirring evenly;

[0014] S2 Preparation of concrete with adjustable air permeability: Add the base material mixture obtained in step S1 to the reactor, then add the pore regulator, heat up and stir, then add the pretreated carbon nanotubes, synthetic fibers and water, after the addition is completed, place the reactor containing the reaction liquid on an ultrasonic vibrator for vibration ultrasound, after the ultrasound is finished, remove the reactor, cast the reaction liquid into shape and perform a curing treatment to obtain concrete with adjustable air permeability.

[0015] Preferably, in the substrate mixing step S1, the stirring speed of the mixer is 1500-2500 rpm.

[0016] Preferably, in the step of preparing concrete with adjustable air permeability in S2, the temperature needs to be raised to 45-50° C. and stirred for 20-40 minutes during the heating and stirring process.

[0017] Preferably, in the step of preparing concrete with adjustable air permeability in S2, the ultrasonic frequency of the ultrasonic vibrator is 33-60 kHz, the ultrasonic vibration duration is 15-30 min, and the ultrasonic vibration requires heating the reactor at a heating temperature of 35-45°C.

[0018] Preferably, the air permeability of the concrete with adjustable air permeability varies within a range of 9 to 75%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention provides a concrete with adjustable air permeability and a preparation method thereof, wherein the raw materials include concrete; inorganic adhesive; mineral particles; pore regulator; carbon nanotubes and synthetic fibers. Concrete, inorganic adhesive and mineral particles are used as base materials, and then pore regulator, carbon nanotubes and synthetic fibers are added at a certain temperature to obtain concrete with adjustable air permeability. Carbon nanotubes and synthetic fibers will form a carbon nanotube fiber thin layer in the base material, and its surface structure can be fine-tuned according to changes in environmental humidity, temperature and the like, thereby changing the air permeability of the material; and the pore regulator is uniformly mixed in the base material, and when the humidity and temperature change, its internal pore structure will change, which will also affect the air permeability. Specifically, when the air humidity is high, the pores inside the concrete will expand, driving the surface carbon nanotube fiber thin layer to expand, thereby increasing the air permeability; and when the humidity is low, the pores inside the concrete will shrink, driving the surface carbon nanotube fiber thin layer to shrink, thereby reducing the air permeability.

[0021] The concrete with adjustable air permeability provided by the present invention also has excellent strength and corrosion resistance, is energy-saving and environmentally friendly, and can meet the long-term use requirements of buildings. DETAILED DESCRIPTION

[0022] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0023] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0024] Embodiment 1: A concrete with adjustable air permeability, comprising the following components in parts by weight:

[0025] 35 parts of concrete; 5 parts of cement; 5 parts of quartz; 3 parts of expanded microspheres; 8 parts of carbon nanotubes; 5 parts of synthetic fibers.

[0026] A method for preparing concrete with adjustable air permeability comprises the following steps:

[0027] S1 substrate mixing: concrete, cement and quartz are added to a mixer in sequence and stirred at a stirring speed of 1500 rpm to obtain a substrate mixture after stirring evenly;

[0028] S2 Preparation of concrete with adjustable air permeability: Add the substrate mixture obtained in step S1 to the reactor, then add the expanded microspheres, raise the reactor temperature to 45°C and stir for 20 minutes. Then add the pretreated carbon nanotubes, synthetic fibers and water, wherein the volume ratio of the mixture to water is 1:1, the diameter of the carbon nanotubes is 10nm, and the length is 20μm. After the addition is completed, place the reactor containing the reaction liquid on an ultrasonic vibrator for ultrasonic vibration. The ultrasonic frequency of the ultrasonic vibrator is 33kHz, and the ultrasonic vibration duration is 15min. The ultrasonic vibration needs to heat the reactor at a heating temperature of 35°C. After the ultrasound is completed, remove the reactor, cast the reaction liquid into shape, and perform a curing treatment to obtain concrete with adjustable air permeability.

[0029] Embodiment 2: A concrete with adjustable air permeability, comprising the following components in parts by weight:

[0030] 42 parts of concrete; 6 parts of cement; 5.5 parts of quartz; 4 parts of expanded microspheres; 9.5 parts of carbon nanotubes; 6.5 parts of synthetic fibers.

[0031] A method for preparing concrete with adjustable air permeability comprises the following steps:

[0032] S1 substrate mixing: concrete, cement and quartz are added to a mixer in sequence and stirred at a stirring speed of 2000 rpm to obtain a substrate mixture after stirring evenly;

[0033] S2 Preparation of concrete with adjustable air permeability: Add the substrate mixture obtained in step S1 to the reactor, then add the expanded microspheres, raise the reactor temperature to 47°C and stir for 30 minutes. Subsequently, add the pretreated carbon nanotubes, synthetic fibers and water, wherein the volume ratio of the mixture to water is 1:2, the diameter of the carbon nanotubes is 30nm, and the length is 50μm. After the addition is completed, place the reactor containing the reaction liquid on an ultrasonic vibrator for ultrasonic vibration. The ultrasonic frequency of the ultrasonic vibrator is 46kHz, and the ultrasonic vibration duration is 22min. The ultrasonic vibration needs to heat the reactor at a heating temperature of 40°C. After the ultrasound is completed, remove the reactor, cast the reaction liquid into shape, and perform a curing treatment to obtain concrete with adjustable air permeability.

[0034] Embodiment 3: A concrete with adjustable air permeability, comprising the following components in parts by weight:

[0035] 50 parts of concrete; 7 parts of cement; 6 parts of quartz; 5 parts of expanded microspheres; 11 parts of carbon nanotubes; 8 parts of synthetic fibers.

[0036] A method for preparing concrete with adjustable air permeability comprises the following steps:

[0037] S1 substrate mixing: concrete, cement and quartz are added to a mixer in sequence and stirred at a stirring speed of 2500 rpm to obtain a substrate mixture after stirring evenly;

[0038] S2 Preparation of concrete with adjustable air permeability: Add the substrate mixture obtained in step S1 to the reactor, then add the expanded microspheres, raise the reactor temperature to 50°C and stir for 40 minutes. Then add the pretreated carbon nanotubes, synthetic fibers and water, wherein the volume ratio of the mixture to water is 1:3, the diameter of the carbon nanotubes is 50nm, and the length is 100μm. After the addition is completed, place the reactor containing the reaction liquid on an ultrasonic vibrator for ultrasonic vibration. The ultrasonic frequency of the ultrasonic vibrator is 60kHz, and the ultrasonic vibration duration is 30min. The ultrasonic vibration needs to heat the reactor at a heating temperature of 45°C. After the ultrasound is completed, remove the reactor, cast the reaction liquid into shape, and perform a curing treatment to obtain concrete with adjustable air permeability.

[0039] Example 4: The cement in Example 2 is replaced with talcum powder; the remaining raw material components, preparation steps and conditions are the same as those in Example 2.

[0040] Example 5: The cement in Example 2 is replaced with kaolin powder; the remaining raw material components, preparation steps and conditions are the same as those in Example 2.

[0041] Example 6: The quartz in Example 4 is replaced by bentonite; the remaining raw material components, preparation steps and conditions are the same as those in Example 4.

[0042] Example 7: The quartz in Example 4 is replaced with a calcium mineral; the remaining raw material components, preparation steps and conditions are the same as those in Example 4.

[0043] Example 8: The expanded microspheres in Example 6 are replaced with ultrafine silicon powder; the remaining raw material components, preparation steps and conditions are the same as those in Example 6.

[0044] Example 9: The expanded microspheres in Example 6 are replaced with a mixture of ultrafine silicon powder and expanded microspheres, wherein the mass ratio of ultrafine silicon powder to expanded microspheres is 3:1; the remaining raw material components, preparation steps and conditions are the same as those in Example 6.

[0045] Example 10: The carbon nanotubes and synthetic fibers in Example 9 are removed; the remaining raw material components, preparation steps and conditions are the same as those in Example 9.

[0046] The air permeability of the concrete with adjustable air permeability prepared in Examples 1 to 10 was tested in an environment with a humidity (RH) of 20%, 50% and 80%. The test data are shown in the following table:

[0047]

[0048] As shown in the test data in the above table, Examples 1 to 3 are to screen the proportions of each component of the raw materials and the parameters in the preparation method, among which Example 2 has the best air permeability adjustment; Examples 2, 4, and 5 are to screen the inorganic binder in the raw materials, and it can be obtained that silicate can increase the air permeability of the finished concrete, wherein the adjustment performance is best when talc is selected as the silicate; Examples 4, 6, and 7 are to screen the mineral particles in the raw materials, and it can be obtained that the mineral material with high porosity can increase the air permeability of the finished concrete, wherein the adjustment performance is best when bentonite is selected as the mineral material; Examples 6, 8, and 9 are to screen the pore regulator in the raw materials, and it can be obtained that the pore regulator can increase the air permeability of the finished concrete, wherein the adjustment performance is best when the pore regulator is a mixture of ultrafine silicon powder and expanded microspheres; Example 10 does not add carbon nanotubes and synthetic fibers to the raw materials, and it can be clearly seen that the concrete prepared in Example 10 has poor air permeability adjustment performance. This is because the concrete surface prepared in Example 10 does not form a thin layer of carbon nanotube fibers, and thus cannot be fine-tuned according to changes in ambient humidity, temperature, etc. to change the air permeability of the material.

[0049] The concrete with adjustable air permeability prepared in Example 9 was tested for strength and corrosion resistance. The test results are shown in the following table:

[0050]

[0051]

[0052] It can be seen from the above table that the concrete with adjustable air permeability prepared in Examples 1 to 9 has high compressive strength and good corrosion resistance, and is suitable for many fields.

[0053] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A concrete with adjustable air permeability, characterized in that: It is composed of the following ingredients in parts by weight: 35-50 parts of concrete; 5-7 parts of inorganic adhesive; 5-6 parts of mineral particles; 3-5 parts of pore regulator; 8-11 parts of carbon nanotubes; and 5-8 parts of synthetic fibers.

2. The concrete with adjustable air permeability according to claim 1, characterized in that: The inorganic adhesive is silicate.

3. The concrete with adjustable air permeability according to claim 1, characterized in that: The mineral particles are mineral materials with high porosity, and further selected from quartz, bentonite, and calcareous minerals.

4. The concrete with adjustable air permeability according to claim 1, characterized in that: The pore regulator is expanded microspheres, ultrafine silica fume or a combination thereof.

5. The concrete with adjustable air permeability according to claim 1, characterized in that: The carbon nanotube has a diameter of 10 to 50 nm and a length of 20 to 100 μm.

6. A method for preparing concrete with adjustable air permeability, characterized in that: The following steps are involved: S1 base material mixing: concrete, inorganic adhesive and mineral particles are added to a mixer in sequence and stirred, and a base material mixture is obtained after stirring evenly; S2 Preparation of concrete with adjustable air permeability: Add the base material mixture obtained in step S1 to the reactor, then add the pore regulator, heat up and stir, then add the pretreated carbon nanotubes, synthetic fibers and water, after the addition is completed, place the reactor containing the reaction liquid on an ultrasonic vibrator for vibration ultrasound, after the ultrasound is finished, remove the reactor, cast the reaction liquid into shape and perform a curing treatment to obtain concrete with adjustable air permeability.

7. The method for preparing concrete with adjustable air permeability according to claim 6, characterized in that: In the step S1 of mixing the substrate, the stirring speed of the mixer is 1500-2500 rpm.

8. The method for preparing concrete with adjustable air permeability according to claim 6, characterized in that: In the step of preparing concrete with adjustable air permeability in S2, the temperature needs to be raised to 45-50° C. and stirred for 20-40 minutes during the heating and stirring process.

9. The method for preparing concrete with adjustable air permeability according to claim 6, characterized in that: In the step of preparing concrete with adjustable air permeability in S2, the ultrasonic frequency of the ultrasonic vibrator is 33-60 kHz, the ultrasonic vibration duration is 15-30 min, and the ultrasonic vibration requires heating of the reactor at a temperature of 35-45°C.

10. The concrete with adjustable air permeability according to claim 1, characterized in that: The air permeability of the concrete with adjustable air permeability varies by 9-75%.

Citation Information

Patent Citations

  • Lightweight proppant and method of making same

    CA2494051A1

  • Efficient waterproof dustproof fiber cement board

    CN110028276A

  • High-porosity resin grinding wheel and preparation method thereof

    CN110524439A

  • High-strength prefabricated building material and preparation method thereof

    CN116589242A

  • Material for regulating weight of silica fume per unit volume and method therefor

    JP1995144946A